Development of the Wimshurst Machine as a Learning Media on Static Electricity Material for Junior High Schools - Asrowi, Ridho Hanan; Budi, Esmar; Nasbey, Hadi (Current STEAM and Education Research, 2023)
This research aims to produce a learning media development product in the form of a Wimhurst machine teaching aid that can be used by teachers and students in the physics learning process. This media is expected to improve the knowledge and scientific thinking skills of grade 8 junior high school students in physics lessons on static electricity. This research was conducted in March-June 2014 at the Physics Department Laboratory, FMIPA-UNJ. The research carried out is research and development. This machine (the media) can show electric charge jumps directly from the friction between aluminum foil (sector) and brass as a rake. The results of the Wimhurst machine are learning media in the form of teaching aids that can help teachers in conveying material and can develop science process skills. The results of testing the Wimhurst machine teaching aids can attract students' interest in studying static electricity, so that students can easily understand the concept of static electricity.